AUDIENCE REFLECTIONS ON ELLE WOODS’ CHARACTER THROUGH LANGUAGE STYLE: : A TIKTOK COMMENT ANALYSIS - Irene Carol Christabel (Language Horizon: Journal of Language Studies, 2025)
Social media has become a new space for individuals to express opinions and affection toward film characters, particularly through TikTok comment sections. This study aims to analyze language style (based on Martin Joos’ five-register theory, 1967) and attitudinal expressions (based on Appraisal Theory by Martin & White, 2005) in ten TikTok user comments responding to the Legally Blonde (2001) video clip where Elle Woods declares, “I don’t need back-ups, I’m going to Harvard.” This research employs a qualitative descriptive method using documentation techniques. The findings reveal that most comments use casual register, reflecting the spontaneous and intimate nature of social media interaction. In terms of attitude, the comments display expressions of affect, judgment, and appreciation, with predominantly positive tones. These results suggest that Elle Woods is perceived positively and seen as inspiring, highlighting audiences' emotional connection with fictional characters through digital discourse.